SLOW PYROLYSIS AND CHARACTERIZATION OF SURFACE FUNCTIONAL GROUPS FOR BIOCHAR DERIVED FROM RUBBER WOOD SAWDUST - Shaaban, Azizah; Se, Sian Meng; Mohd Fairuz, Dimin; Hamid, Nadiah (2013)
Rubber wood sawdust (RWSD), an agricultural by-product generated from conversion of wood logs to sawn timber in the rubber wood industry. It is utilized as the low or zero cost starting material for the preparation of biochar to be applied as soil amendment. Prior to the pyrolysis process of raw RWSD, carbon-hydrogen-nitrogen (CHN) analysis and thermal gravimetric analysis were carried out for elemental and thermal stability analysis respectively. The biochar is pyrolyzed by using a conventional tube furnace heated at temperature between 300°C to 700°C at a heating rate of 5°C/min for 3 hours under the flow of nitrogen gas. The pyrolyzed materials were ground into fine powder for X-ray Diffraction (XRD) analysis, alkalinity test, Fourier Transform Infrared spectroscopy (FTIR) and Boehm titration. The FTIR spectra showed the amount of functional groups reduce with the increase of heating temperatures. The increase in temperature also caused the surface negative charge of biochar reduced from 1.3mmol/g to 0.3mmol/g as detected by Boehm titration test with 0.1N natrium hydroxide (NaOH) solution. These results might be due to the reduction of functional groups such as carboxyl, lactone and phenol groups through thermal decomposition process.